Two «inventions»: The Christ of help by Martínez Montañés and the Philip IV on horseback. Origins and architectonic effects during their diffussion in Lima - Mattos-Cárdenas, Leonardo (2019)
In the following essay, two masterpieces by Juan Martínez Montañés (1568-1649) are analysed: his famous sculpture of the Crucified (1603), which was destined for a retable at the church of Our Lady of Mercy in Lima and whose original pictorical version (already recuperated) gave origin to an engraving (1739), and his partial contribution to the Philip IV on horseback; confronting the iconographic fortune of both “inventions” and their little-known presence in the urban scenery of Lima.